ANALISIS KEBUTUHAN NARAPIDANA PEREMPUAN SEBAGAI KELOMPOK RENTAN DI LEMBAGA PEMASYARAKATAN - Subroto, Mitro; Christoffel, Gilberth (Ensiklopedia Sosial Review, 2024)
Abstract: This study explores the needs of female inmates, a vulnerable group within correctional facilities, highlighting the urgency of addressing their specific requirements. Female inmates often face unique challenges, including mental health issues, lack of access to healthcare, and insufficient rehabilitation programs. Utilizing a qualitative research approach, data were collected through interviews and focus group discussions with female inmates and correctional staff. The findings reveal significant gaps in the provision of healthcare services, educational opportunities, and psychological support for female inmates. The study concludes that targeted policies and programs are essential to meet the needs of female inmates, ensuring their rights and facilitating successful reintegration into society.